Failure Analysis of the Screw Press Machine - Dedi Wardianto; Anrinal (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) - ITP, 2022)
In this paper, an analysis of the mechanical components of the Screw Press Machine is carried out in the form of an analysis of the design of mechanical components, maintenance cycles and remaining life. From the design analysis of mechanical components, it is known that the stresses that occur in the screw are in the form of nominal shear stresses of 18.18 N/mm², axial stresses of -10.41 N/mm², bending stresses of 54.66 N/mm², and shear stresses acting on the base screw of 65.41 N/mm². The number of press cycles that occur in one hour is 121 cycles. Number in the press cycle that occurs in the worm screw press is 2.625x105 cycles. In field conditions with pressure fluctuating between 30-40 bars, the life time of using a worm screw press is around 2169.43 hours.